Tantangan Pembelajaran: Teknologi Sel Surya dalam Pembelajaran PjBL-STEM Menggunakan Strategi Jigsaw untuk Meningkatkan Keterampilan Abad 21 Siswa Kelas 9 - Rida Widiawati; Anna Permanasari; Didit Ardianto (Postgraduate, University of Mataram, 2023)
Project-based innovative, creative, and integrative learning is currently an option in preparing 21st-century skills for students and accommodating the implementation of the Merdeka Belajar Curriculum. Research has been conducted through the application of PjBL-STEM learning with a Jigsaw strategy through the theme of environmentally friendly technology with the utilization of solar cells in grade 9 to improve critical thinking skills and communication skills. This research was conducted using a pseudo-experimental method with a pre-posttest control group design using inferential analysis methods to test critical thinking skills while testing communication skills using descriptive analysis. The research subjects were junior high school students totaling 62 people. The results showed that PjBL-STEM learning with the Jigsaw strategy can train students to argue, draw conclusions, deduce, and build basic skills, tactics, and strategies better than the control class. The Jigsaw strategy causes students to become more confident and trained to discuss more intensely with both the initial group and the expert group. This led to an increase in students' communication skills much better than the control class students whose learning was guided by the inquiry method